Susceptibility of methicillin-resistant Staphylococcus aureus to lysostaphin. - Huber, M M (1989)
One hundred and eleven isolates of methicillin-resistant Staphylococcus aureus recovered from patients at the Olin E. Teague Veterans Center from March 1983 to April 1987 were as susceptible to lysis by lysostaphin as methicillin-susceptible S. aureus controls were.